Rancang Bangun Sistem Manajemen Palang Parkir AI-IoT Otomatis Menggunakan YOLO & OCR - Chandrawan, Maria Angelica; Tanamal, Edgar; Prasetya , Antonius Indra Dharma; Syariati, Kasmir; Suardi, Citra (JTRISTE, 2023)
Humans and civilization cannot be separated from technological developments. The Internet of Things (IoT) is one type of developing technology that can help and meet everyday needs. The IoT can be used in various fields. One of them in the field of transportation is the parking service system. The problem that is often encountered when visiting a special place such as a mall, apartment, or offices on holidays or holidays is that drivers find it difficult to find a parking space. Based on this description, in this study we designed an automated AI-IoT-based crossbar management system using YOLO and OCR. From this study we obtained satisfactory results regarding the use of YOLOv4 and OCR to detect vehicle plates with a high accuracy rate of 98.75%.